The Role of Integrating Strategic Management Accounting with Big Data and Artificial Intelligence in Enhancing Financial Analysis and Decision-Making - Alimuddin, Alimuddin; Usman, Asri; Abbas, Aulia Thalita Sada; Fadila, Nuriya (Journal of Comprehensive Science, 2025)
This study aims to systematically analyze the crucial role of integrating Strategic Management Accounting with Big Data and Artificial Intelligence (AI) in enhancing financial analysis capabilities and the effectiveness of strategic decision-making. Using the Systematic Literature Review (SLR) approach, this study synthesizes the findings of 29 relevant scientific articles indexed in the Scopus database from 2014 to 2024, identified through the keywords "strategic management accounting, big data, and artificial intelligence." The results of the analysis demonstrate that this integration fundamentally transforms financial analysis, making it more predictive, accurate, and real-time, while also accelerating and improving the quality of data-driven decision-making. Moreover, these findings reveal a shift in the role of accountants from operational functions to strategic advisors, necessitating proficiency in analytical skills and technological literacy. It can be concluded that the synergy between strategic management accounting, Big Data, and AI serves as a key driver of competitive advantage. However, its success is highly dependent on the organization's ability to address challenges such as skills gaps, ethical risks, and the critical importance of implementing robust information technology governance as an essential mediating factor.